2011
DOI: 10.1126/science.1203165
|View full text |Cite
|
Sign up to set email alerts
|

A Pericyte Origin of Spinal Cord Scar Tissue

Abstract: There is limited regeneration of lost tissue after central nervous system injury, and the lesion is sealed with a scar. The role of the scar, which often is referred to as the glial scar because of its abundance of astrocytes, is complex and has been discussed for more than a century. Here we show that a specific pericyte subtype gives rise to scar-forming stromal cells, which outnumber astrocytes, in the injured spinal cord. Blocking the generation of progeny by this pericyte subtype results in failure to sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
763
10
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(836 citation statements)
references
References 31 publications
35
763
10
2
Order By: Relevance
“…Additionally, a recent study by Kan et al (2013) identified that cells presenting the glutamate transporter GLAST were found to contribute to the formation of ectopic bone, and that these GLAST + cells appeared to be distinct from the Tie2 + population identified by Woscyzna et al (2012) [94]. Pericyte populations have been shown to express GLAST [99], and consequently this information further highlighted the potential role of these cells during HO. However, due to a lack of novel surface markers that can be used for the definitive phenotypic characterisation of pericytes in vivo, the role of these cells in HO remains elusive.…”
Section: Neural Crest Pericytesmentioning
confidence: 88%
“…Additionally, a recent study by Kan et al (2013) identified that cells presenting the glutamate transporter GLAST were found to contribute to the formation of ectopic bone, and that these GLAST + cells appeared to be distinct from the Tie2 + population identified by Woscyzna et al (2012) [94]. Pericyte populations have been shown to express GLAST [99], and consequently this information further highlighted the potential role of these cells during HO. However, due to a lack of novel surface markers that can be used for the definitive phenotypic characterisation of pericytes in vivo, the role of these cells in HO remains elusive.…”
Section: Neural Crest Pericytesmentioning
confidence: 88%
“…The PDGFRb þ CD105 þ cells observed in the ischemic brain tissue are likely stromal cells derived from 'type A' PCs, which have recently been reported to proliferate and seal the tissue defect after surgical lesion of the spinal cord. 17 The authors of this important study were able to track the origin of PDGFRb þ cells to mural cells, which express both PDGFRb and CD13.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that, far from being a mere collection of debris, the ischemic CNS tissue exhibits a surprisingly high degree of remodeling in rodents and humans. Although scarring may seal the injured tissue after dorsal funiculus incision or dorsal hemisection of the spinal cord in mice, 17 the generation of excessive ECM may also negatively affect the structure and function of organs. 27 In the injured CNS, fibroblast-like stromal cells may impede axonal outgrowth by expressing semaphorin3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may thus be that the decreased activity of caspase 3/7 in response to monomer Aβ1‐40 seen in our study contributes to both the increased cell viability and the increased cell division. Finally, it is important to point out that cell cultures can never replicate a biological system and although pericyte proliferation does occur in the human brain (Fernandez‐Klett et al., 2013; Goritz et al., 2011; Matsushita et al., 2015; Paul et al., 2012), the conditions and rate in the brain are not comparable to the same in a Petri dish. Hence, we would like to stress that our cell model is useful foremost as a tool to demonstrate that differences in pericyte response to Aβ depend on both aggregation form and specie.…”
Section: Discussionmentioning
confidence: 99%